Information System for Optimizing Inventory Management with The Average Method in Modern Retail Business - Kusumawati, Dara; Winarno, Basuki Heri; Noor M, Ardiansyah Restu (Universitas Syiah Kuala, 2025)
Merchandise inventory is something important for companies, especially for retail businesses because merchandise inventory is a component of current assets that has a high level of liquidity, so recording and managing inventory is an important component for retail businesses. Amazon stores sell quite lots of types and quantities of merchandise, and the recording of merchandise inventory is still done manually, making it possible for recording errors to occur which results in inaccurate reports being produced, resulting in inaccurate decision making related to inventory. Besides that, it is also difficult to know the amount of inventory, purchases and sales of merchandise at any time. Based on the problems in the Amazon store, it is necessary to have an information system for recording and managing merchandise inventory, so that it can assist in recording purchases, sales, and making decisions regarding inventory in the Amazon store. The merchandise inventory information system using the average method created can help Amazon stores to record sales transactions, purchase transactions, supplier data, goods data and can produce expected reports such as sales reports, purchase reports, warehouse cards and inventory cards using the average method and reduce the risk of losing data related to the inventory held by Amazon stores.